2016
DOI: 10.1074/jbc.m116.722751
|View full text |Cite
|
Sign up to set email alerts
|

Ajuba Phosphorylation by CDK1 Promotes Cell Proliferation and Tumorigenesis

Abstract: Recent studies identified the adaptor protein Ajuba as a positive regulator of Yes-associated protein (YAP) oncogenic activity through inhibiting large tumor suppressor (Lats1/2) core kinases of the Hippo pathway, a signaling pathway that plays important roles in cancer. In this study, we define a novel mechanism for phospho-regulation of Ajuba in mitosis and its biological significance in cancer. We found that Ajuba is phosphorylated in vitro and in vivo by cyclin-dependent kinase 1 (CDK1) at Ser 119 and Ser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…During these experiments, we found that MST2, but not MST1, was upshifted on a SDS-polyacrylamide gel during G2/M arrest (Fig. 1A, B) [16]. Lambda phosphatase treatment largely abolished the mobility upshift of MST2, suggesting that MST2 is phosphorylated during G2/M arrest (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…During these experiments, we found that MST2, but not MST1, was upshifted on a SDS-polyacrylamide gel during G2/M arrest (Fig. 1A, B) [16]. Lambda phosphatase treatment largely abolished the mobility upshift of MST2, suggesting that MST2 is phosphorylated during G2/M arrest (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Phos-tag ™ was obtained from Wako Pure Chemical Industries, Ltd. (304-93521) and used at 20 μM (with 100 μM MnCl 2 ) in 8% SDS-polyacrylamide gels as we previously described [16]. Western blotting, immunoprecipitation, and lambda phosphatase treatment assays were done as previously described [15,22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ajuba (Jub), a regulator of Aurora A kinase (36,37), was one of the strongest candidates in this cluster, with a 3-fold reduction in GSK-3-dependent phosphorylation at serine 129 (Fig. 3B), a site previously shown to be phosphorylated by other protein kinases to regulate entry into mitosis (37,38). Septin-9 (SEPT9), a member of the septin family of cytoskeletal proteins that regulates multiple functions, including cytokinesis and chromosome segregation (39,40), is phosphorylated at serine 85, also a GSK-3 consensus site, and this phosphorylation was reduced almost 2-fold in DKO ESCs.…”
Section: Gsk-3 Phosphoproteomementioning
confidence: 99%
“…Phos-tag ™ was obtained from Wako Pure Chemical Industries, Ltd. (cat#: 304-93521) and used at 10–20 μM (with 100 μM MnCl 2 ) in 8% SDS-acrylamide gels as described [29]. Western blotting and lambda phosphatase treatment assays were done as previously described [25].…”
Section: Methodsmentioning
confidence: 99%